The world encyclopedia / Trivia questions and answers - Anuj chawla; Lata seth. (New Delhi : Dreamland publications, 2023)
Designed and compiled by experts, this book will educate and illuminate young readers as they get answers to all the questions they wanted to know. It is a useful resource for curious learners to find more about their world.
All About The World Encyclopedia$1 (B. Filled with dynamic questions that expand the curious kids' minds and spark discussion this book has reliable answers to vivid questions.s
Includes index.
Keywords: Children - Science and Technology; Nature and Amazing places; Around the world